Demographic and preliminary employment data of the first two graduate cohorts from a rural veterinary school. Issue 4 (April 2017) - Hyams, JH; Raidal, SL; Hayes, LM; Heller, J
Abstract : Objective: To report initial career experiences and graduate employment destinations 1 and 5 years following graduation of the 67 graduates from the first two graduating classes of the veterinary science program at Charles Sturt University. Design: Online survey of graduates from the 2010 and 2011 cohorts undertaken 12 months following course completion and descriptive data on graduate practice locations 5 years post‐graduation. Procedure: Questions covered general demographic information, issues relating to work–life balance and factors influencing vocational choices. Descriptive statistics and qualitative responses are reported, with comparisons between continuous variables by two‐sample t‐test and between categories by Chi‐square analyses. Significance was set at P < 0.05. Graduates' locations 5 years after graduation were obtained from veterinary registration details and staff contact with graduates. Results: Complete survey responses were received from 39 graduates of whom 34 were employed in regional areas, 1 in a very remote area, 3 in major cities and 1 overseas. Hours worked and salary received were consistent with other survey data, with new graduates working in regional practices earning slightly more than those working in metropolitan practices. At 5 years following graduation, the majority (56/61, 92%) remained in rural or regional Australian veterinary practices, with a further five graduates overseas and one lost to follow‐up. Conclusion: This study supported the selection criteria and educational approaches at CSU in establishing most of the new graduates in rural and regional mixed veterinary practice.